Analysis of Transformational Leadership Style in Employee Work Engagement at the Faculty of Economics Universitas Nias - Zebua, Sabar Gunawan; Hulu, Fatolosa (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research analyzes the implementation of transformational leadership style and its role in enhancing employee work engagement at the Faculty of Economics, Universitas Nias. Using a qualitative descriptive approach, data were collected through in-depth interviews with five key informants, including the Dean, Vice Deans, Head of Study Program, and staff, complemented by observation and documentation from June to November 2025. Findings reveal that transformational leadership has been implemented through four dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. However, implementation faces multidimensional constraints, including varied employee readiness for change, limited resources, workload imbalance, coordination challenges, suboptimal reward systems, insufficient monitoring mechanisms, and a persistent conventional work culture. Despite these obstacles, employee engagement remains relatively high, characterized by strong vigor, dedication, and absorption. The research proposes twelve strategic initiatives to optimize transformational leadership effectiveness: strengthening internal communication systems, developing systematic capacity building programs, establishing transparent reward mechanisms, enhancing employee empowerment through delegation, creating conducive work environments, building structured monitoring systems, strengthening cross-unit collaboration, redistributing workload equitably, implementing systematic change management, establishing mentoring programs, fostering innovation culture, and developing external partnerships. The regional independence ratio of only 2.59% indicates minimal fiscal capacity, underscoring the need for comprehensive long-term strategies to enable meaningful organizational transformation.